Pembinaan Guru Madrasah Ibtidaiyah (MI) dalam Implementasi Deep Learning pada Kurikulum Merdeka - Novan, Novan Ardy Wiyani; Rina, Rina Rizki Amalia (Dharmahita: Journal of Community Service and Development, 2025)
At the beginning of the 2025/2026 school year, teachers at Islamic Elementary Schools (MI) began implementing the deep learning approach within the Merdeka Curriculum, including teachers in Rembang District, Purbalingga Regency, Central Java. However, unfortunately, not all teachers have the skills to implement deep learning within the Merdeka Curriculum. This community service activity aims to describe the implementation of MI teacher guidance in implementing deep learning within the Merdeka Curriculum. This community service activity was conducted using the service learning method. Data was collected through interviews and documentation. The community service activity was carried out in four stages. First, identifying the needs of MI teachers in implementing deep learning within the Merdeka Curriculum. Second, designing coaching materials based on the results of the needs identification. Third, delivering material on the concept of deep learning within the Merdeka Curriculum through educational seminars. Fourth, diagnosing and providing solutions to the difficulties faced by MI teachers in implementing deep learning within the Merdeka Curriculum through interactive dialogue activities during educational seminars.